Transapical electrosurgical laceration and stabilization of mitral clips followed by transcatheter mitral valve replacement—A one-stop shopCentral MessagePerspective - Joerg Kellermair, MD; Ilinca Damian, MD; Michael Grund, MD; Georg Hagleitner, MD; Florian Huber, MD; Michael Resl, MD; Gregor Sulzbacher, MD; Martin Clodi, MD; Clemens Steinwender, MD; Andreas Zierer, MD (JTCVS Techniques)
Objective: Electrosurgical laceration and stabilization of mitral clips (ELASTA-CLIP) is a bail-out technique to recreate a single-orifice mitral valve after transcatheter edge-to-edge repair (TEER) with subsequent transcatheter mitral valve replacement (TMVR). This technique is a novel option for patients with significant residual mitral regurgitation after TEER with high risk for conventional surgery. The original ELASTA CLIP procedure features a transseptal approach, whereas the TMVR with the Tendyne bioprosthesis has a transapical access. Hereby we tested the hypothesis that a modified transapical ELASTA CLIP technique can be safely applied transapically allowing a straightforward one-stop shop access strategy. Methods: We developed the procedural steps in a porcine passive-beating heart model and applied the modified technique with subsequent TMVR in 2 consecutive patients with severe mitral regurgitation after previous TEER. Patients were followed up to 30 days. Results: The modified transapical ELASTA CLIP procedure was successful in both patients. The mean total procedure time was 118 minutes, and the mean fluoroscopy duration 22 minutes. At 30 days’ follow-up, both patients were alive without bleeding complications, reintervention, or prosthetic valve dysfunction. Conclusions: The modified transapical ELASTA CLIP procedure is technically feasible and safe at 30 days. Procedure times are lower compared with previous reports of the original transseptal approach.